2017
DOI: 10.1186/s12989-017-0222-4
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric analysis of anti-proliferative and apoptotic effects of gold nanoprisms on mouse and human primary and transformed cells, biodistribution and toxicity in vivo

Abstract: BackgroundThe special physicochemical properties of gold nanoprisms make them very useful for biomedical applications including biosensing and cancer therapy. However, it is not clear how gold nanoprisms may affect cellular physiology including viability and other critical functions. We report a multiparametric investigation on the impact of gold-nanoprisms on mice and human, transformed and primary cells as well as tissue distribution and toxicity in vivo after parental injection.MethodsCellular uptake of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 58 publications
3
14
0
Order By: Relevance
“…Increased oxidative stress has been suggested to be the major cause of organ toxicity [ 40 ]. Increased ROS production appeared in macrophages treated with high concentration of AuNP in line with reduced cell viability, consistent with the literature [ 41 , 42 ]; however such changes diminished with the co-culture with adipocytes suggesting unknown antioxidative mechanism due to the interaction between these two cell types. Similarly, AuNP treatment of adipocytes cultured alone did not change their differentiation rate into mature adipocytes, nor metabolic markers.…”
Section: Discussionsupporting
confidence: 91%
“…Increased oxidative stress has been suggested to be the major cause of organ toxicity [ 40 ]. Increased ROS production appeared in macrophages treated with high concentration of AuNP in line with reduced cell viability, consistent with the literature [ 41 , 42 ]; however such changes diminished with the co-culture with adipocytes suggesting unknown antioxidative mechanism due to the interaction between these two cell types. Similarly, AuNP treatment of adipocytes cultured alone did not change their differentiation rate into mature adipocytes, nor metabolic markers.…”
Section: Discussionsupporting
confidence: 91%
“…Both the visualization of the tissues by H&E staining (Figure 2a) and the weight monitoring (Figure 2b) showed neither significant changes in terms of weight, nor drastic microscopic alterations in the organ morphology compared with the control groups. However, a considerable microvesicular steatosis was observed in the liver at the groups with the maximum gold signal, which was also observed in a previous study [30]. Moreover, these microscopic alterations were correlated with a significant splenomegaly during the first 24 h post injection.…”
Section: Lspr and ζ-Potential Of Nanoparticles In Saline And Mouse Serumsupporting
confidence: 86%
“…The lack of toxicity of the nanoparticles was studied in vitro in our previous research (Alfranca, Artiga et al, 2016) as well as collaborators [30]. During the in vivo studies described herein, the low toxicity was further confirmed by monitoring the changes in the weight of the mice, by hematoxylin-eosin staining (H&E) of the tissues and also by monitoring the changes in weight of the organs collected.…”
Section: Biocompatibilitymentioning
confidence: 73%
“…Despite a difference in the degree of autophagy, SiO 2 NPs still induced significant levels of autophagy, but this has no effect whatsoever on the cytoskeletal network. Previous studies have reported clear effects of various NPs including iron oxide, silver and gold on cell size and cytoskeletal network, predominantly affecting actin fibers [ 6 , 44 47 ], while this effect was not observed for silica NPs [ 48 ]. Silica NPs have however been observed to affect tubulin fibers [ 49 ].…”
Section: Resultsmentioning
confidence: 99%